Profile of children with increased intracranial pressure on mannitol treatment - Sander D Teddy; Abdul Latief; Bambang Madiyono (Indonesian Pediatric Society, 2004)
Background Early recognition of increased intracranial pressure(IIP) and well-monitored management are determining indicatorsfor treatment outcome. As far as we know, data of children with IIPon mannitol treatment has not been available.Objective To elicit the profile of IIP patients who received mannitolat the Department of Child Health, Cipto Mangunkusumo Hospital,Jakarta.Methods This was a cross-sectional study. Data were obtainedfrom medical records of patients with increased intracranial pres-sure who received mannitol at the Department of Child Health,Cipto Mangunkusumo Hospital, Jakarta between July 2001 to Oc-tober 2003Results Fifty-four IIP patients with mannitol treatment were included.Forty-two (78%) were under-five years old. Thirty-six subjects (67%)were boys; 30 (56%) were undernourished. Central nervous systeminfections (meningitis and encephalitis) were the most frequent causesof IIP. Most of the head CT scan revealed cerebral edema, hydroceph-alus, and cerebral hemorrhage. Fifty subjects (93%) had decline of con-sciousness; most of them were somnolent. Improvement in conscious-ness was identified in 31 subjects, in which 21 subjects reached fullconsciousness. Vomiting, which was found in 25 subjects (46%), sub-sided after mannitol administration. Behavioral changes were found in49 subjects (91%); 32 subjects still had persistent behavioral changesafter mannitol administration. Large and protruding fontanel was foundin 7/22 subjects, cerebral nerve paralysis in 23 subjects (43%) andpapillary edema in 6 of 34 subjects who underwent funduscopy. Duringthe treatment with mannitol, fever was found in 5 subjects, vomiting in 2subjects, skin edema and tachycardia each in 1 subject. Metabolic aci-dosis was found in 6/13 subjects, hyponatremia and hypokalemia in 16and 13 out of 30 subjects respectively. Death occurred in 9 subjects(17%).Conclusion In IIP patients, the administration of mannitol has atendency to improve consciousness, vomiting, and behavioral orpersonality changes. The high incidence rate of electrolyte imbal-ances and metabolic acidosis during the treatment indicated theneed of periodic monitoring to detect early disorders.